Training on Using Microsoft Word to Support AKM Success for Grade 5 Students at SDN 1-2 Cibunar - Didin Sahidin; Arief Loekman; Ninah Hasanah; Nanan Nugraha; Putri Hermayanti (Fakultas Kewirausahaan Universitas Garut, 2021)
Abstract Cibunar Village is one of the villages in Tarogong Kidul District, Garut Regency, West Java. Here there are two elementary schools with limited availability of supporting facilities for formal education and extra activities. The ability to use Microsoft Word is one of the factors that can support the success of AKM, therefore training activities on the use of Microsoft Word for 5th grade students of SDN 1-2 Cibunar are very much needed. This activity aims to provide education about the use of Microsoft Word. This activity is carried out using a simple material presentation and practice method. The results of the training show that the average pre-test score of participants is 30.00 while the average post-test score of participants is 75.00. These results indicate that the training activities have an impact on increasing participants' understanding and skills in using computers and operating Microsoft Word applications. Abstrak Desa Cibunar merupakan salah satu desa yang ada di Kecamatan Tarogong Kidul Kabupaten Garut Jawa Barat. Di sini terdapat dua buah Sekolah Dasar yang ketersediaan fasilitas pendukung pendidikan formal dan kegiatan ekstra yang terbatas. Kemampuan pada penggunaan Microsoft Word merupakan salah satu faktor yang dapat menunjang keberhasilan AKM, oleh karena itu kegiatan pelatihan penggunaan Microsoft Word untuk siswa kelas 5 SDN 1-2 Cibunar sangat dibutuhkan. Kegiatan ini bertujuan memberikan edukasi tentang penggunaan Microsoft Word. Kegiatan ini dilaksanakan dengan metode presentasi materi dan praktik sederhana. Hasil pelatihan menunjukan nilai rata-rata pre test peserta adalah 30,00 sedangkan nilai rata- rata post test peserta adalah 75,00. Hasil tersebut menunjukan bahwa kegiatan pelatihan menunjukan adanya dampak peningkatan dalam pemahaman dan keterampilan peserta dalam penggunaan komputer dan pengoperasian aplikasi Microsft Word.